Hubungan Status Fungsional dengan Kualitas Hidup Pasien Pasca Stroke - Ika Ariyanti; Mula Tarigan; Hasnida Hasnida (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the relationship between functional status and quality of life of post-stroke patients. This research method is a correlation study using a quantitative approach. Convenience sampling research sampling technique. The number of samples is 81 post-stroke patient respondents. The research was conducted at the Outpatient Clinic of Haji Adam Malik General Hospital, Medan. Demographic data were analyzed univariate to determine the distribution of the frequency characteristics of the respondents. Bivariate analysis used bathel's index to measure functional status and the mos (SF-36) to measure quality of life. The results showed that the p-value was 0.53 > 0.05 with a correlation coefficient (r) of 0.07 which indicated that there was no relationship between functional status and the quality of life of post-stroke patients. In conclusion, there is no relationship between functional status and quality of life of post-stroke patients. Keywords : Functional Status, Post Stroke, Quality of Life.